Keberlanjutan dari Hutan: Bagaimana Pasang Ri Kajang Mempengaruhi Regulasi Lingkungan Modern - Nurfatimah, N; Risma Handayani; Nursyamsi Faradillah (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
This study examines the integration of Pasang Ri Kajang into Regional Regulation (Perda) No. 9 of 2015 of Bulukumba Regency and its relevance to sustainable development within the Ammatoa Kajang Indigenous Community. Pasang Ri Kajang, as the philosophical foundation of the community, embodies ecological ethics, social norms, and moral values that regulate human interaction with nature. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation involving customary leaders, community members, and local government officials. The findings indicate that Perda No. 9/2015 functions as a formal instrument that institutionalizes the values of Pasang, particularly in protecting customary land rights, preserving cultural traditions, and managing customary forests through conservation principles. This integration produces a hybrid governance model that combines the moral legitimacy of customary norms with the legal certainty of state regulation. The implementation of the regulation contributes positively to ecological, social, and economic sustainability, although it still faces challenges such as modernization pressures, land-use conversion, and weak policy enforcement. Overall, the study highlights the crucial role of Pasang Ri Kajang in strengthening sustainable environmental governance at the local level.